Pengaruh Tipe Kepribadian, Pengalaman dan Penerimaan Perilaku Disfungsional Terhadap Audit Judgement - Fikri Ismail (Faculty of Economic and Business, 2015)
This research was aimed to obtain empirical evident whether there is any effect of personality type, auditor’s experience and acceptance of dysfunctional behavior toward audit judgment taken by auditor. This research was carried out in DKI Jakarta with respondent from auditors who work in Public Accountant Office in DKI Jakarta. The sampling technique is used convenience sampling. Data is collected using questionnaires distributed as 79 and only 51 questionnaires that can be processed. Data analysis using multiple linear regression. The results of this study showed that : (1) personality type didn’t has significant effects on audit judgment. (2) auditor’s experience has significant effects on audit judgment. (3) acceptance of dysfunctional behavior has significant effects on audit judgment. (4) personality type, auditor’s experience and acceptance of dysfunctional behavior have significant effects on audit judgment simultaneously.DOI: 10.15408/ess.v5i2.2348